UJI MEKANIK KERANGKA TURBIN ULIR ARCHIMEDES UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Nuriman, Lutfi (Politeknik Harapan Bersama Tegal, 2023)
Abstract – The development of Indonesia's population can increase the demand for electricity. Therefore, it is necessary to conduct research on the development of micro-hydro power plants. This is one of the best solutions to overcome the energy crisis. In creating a turbine, it is necessary to pay attention to the resistance of the frame to corrosion, one of which is SS 304 steel. SS 304 is a material that is resistant to corrosion. This study aims to determine the mechanical properties of SS material in the process of tensile testing, hardness testing, and composition testing. The tensile test method used the Universal Testing Machine, the hardness test used the Brinell hardness Tester, and the composition test used the ARL Optic Emission Spectrometer Switzerland. From the results of tensile testing specimens I, II and III have an average value (Max Stress) of 587,519 N/mm2 , (YP Stress) of 360,778 N/mm2 . It was concluded that the best tensile strength in specimen I with a tensile strength of 680.43 N/mm2 and yield strength of 371.997 N/mm2 . The hardness test results for the hardest point at point III with a hardness value of 167 HB, while the lowest hardness value is at point 1 and point 2 with a hardness value of 165 HB. Testing the elemental composition of the highest SS 304 content was found in Croom (C) and Nickel (Ni) with Croom (C) = 18.18%, and Nickel (Ni) = 8.575 %.